Nematode resistance to ivermectin (630 and 700 mu g/kg) in cattle from the Southeast and South of Brazil - Felippelli, Gustavo [UNESP]; Zanetti Lopes, Welber Daniel [UNESP]; Cruz, Breno Cayeiro [UNESP]; Pires Teixeira, Weslen Fabricio [UNESP]; Maciel, Willian Giquelin [UNESP]; Favero, Flavia Carolina [UNESP]; Buzzulini, Carolina [UNESP]; Sakamoto, Claudio [UNESP]; Soares, Vando Edesio [UNESP]; Costa Gomes, Lucas Vinicius [UNESP]; Oliveira, Gilson Pereira de [UNESP]; Costa, Alvimar Jose da [UNESP] (Elsevier B.V., 2014)
Two high doses of ivermectin (630 mu g/kg and 700 mu g/kg) that are sold commercially in Brazil were evaluated in dose-and-slaughter trials with 144 naturally nematode-infected cattle from eight regions within the states of Minas Gerias, Sao Paulo and Rio Grande do Sul in Brazil. Treatment groups were based on fecal egg counts 1, 2, and 3 days before treatment; all animals studied had a minimum egg count of at least 500 eggs per gram of feces (EPG). Post-mortem analyses were conducted on day 14. The highest levels of resistance to ivermectin were found for Haemonchus placei, Cooperia punctata and Oesophagostomum radiatum; all populations of H. placei were resistant to the 630 mu g/kg dose, and 67% were resistant to 700 mu g/kg; 86% of C. punctata were resistant to the 630 mu g/kg dose, and 33% were resistant to 700 mu g/kg. A combined analysis revealed that 57% of O. radiatum were resistant to the lower dose of ivermectin. H. placei, C. punctata and O. radiatum, in order, were the nematode populations with the highest indices of resistance, whereas Trichostrongylus axei was the most susceptible to 630 and 700 mu g/kg dosages of ivermectin. The results of helminthic resistance to ivermectin for different populations of H. placei and C. punctata described in the present study support previous literature data, in which a small decrease in the average parasitic burden of C. punctata and a consequent increase of H. placei were observed in cattle from the Southeast, South and Center-West regions of Brazil. (C) 2014 Elsevier Ireland Ltd. All rights reserved.
Keywords: Bovines; Helminths; High concentration; Ivermectin; Resistance